An Influenza HA and M2e Based Vaccine Delivered by a Novel Attenuated Salmonella Mutant Protects Mice against Homologous H1N1 Infection - Hajam, Irshad A.; Lee, John H. (Frontiers in Microbiology, 2017)
Attenuated Salmonella strains constitute a promising technology for the development of a more efficient multivalent protein based vaccines. In this study, we constructed a novel attenuated strain of Salmonella for the delivery and expression of the H1N1 hemagglutinin (HA) and the conserved extracellular domain of the matrix protein 2 (M2e). We demonstrated that the constructed Salmonella strain exhibited efficient HA and M2e protein expressions and little cytotoxicity and pathogenicity in mice. Using BALB/c mice as the model, we showed that the mice vaccinated with a Salmonella strain expressing HA and M2e protein antigens, respectively, induced significant production of HA and M2e-specific serum IgG1 and IgG2a responses, and of anti-HA interferon-γ producing T cells. Furthermore, immunization with Salmonella-HA-M2e-based vaccine via different routes provided protection in 66.66% orally, 100% intramuscularly and 100% intraperitoneally immunized mice against the homologous H1N1 virus while none of the animals survived treated with either the PBS or the Salmonella carrying empty expression vector. Ex vivo stimulated dendritic cells (DCs) with heat killed Salmonella expressing HA demonstrated that DCs play an important role in the elicitation of HA-specific humoral immune responses in mice. In summary, Salmonella-HA-M2e-based vaccine elicits efficient antigen-specific humoral and cellular immune responses, and provides significant immune protection against a highly pathogenic H1N1 influenza virus.